Physicochemical properties of bacterial cellulose formed by the novel Komagataeibacter xylinus C-3 strain on an optimized nutrient medium (Experimental biology, 2017)
Bacterial cellulose (BC) - a natural polymer, characterized by high adsorption capacity, biocompatibility and mechanical strength. Unlike plant cellulose, BC is a chemically pure extracellular product. Due to its unique properties BC is a promising material for medicine.Studies on development and application of BC in field of medical materials science are conducted in many countries. However, the obtaining of BC in Kazakhstan has not been established yet, and there are no strains in collections for its production on an industrial scale.The purpose of present study was to isolate the bacterial cellulose producer and to select optimal conditions for its growth and BC gel film biosynthesis under surface cultivation conditions.Bacterial cellulose-producing strains were isolated from a mixed culture of Kombucha, as well as apple cider vinegar of «El-iksir» firm on S. Hestrin, M. Shramm media. The optimization factors of nutrient medium were the upper and lower concentration levels of glucose, beer wort and ethanol. The productivity of strains was assessed by measuring the BC mass, which was previously dried at 80 °C. The culture-morphological properties of isolated strain were studied using a BIOLAM laboratory microscope. For biochemical identification of strains, a Vitek bacterial analyzer (BioMerieux, France) with standardized API 50 CH and API 20 E test systems with Apiweb identification software was used. The strain species and purity on extraneous contamination was determined by analyzing the nucleotide sequence of 16S rRNA gene. A study of films structure was studied on a scanning electron microscope. The mechanical strength of BC was determined on an «Instron» testing machine.A new producer of bacterial cellulose Komagataeibacter xylinus C-3 was isolated, identified and genotyped. The parameters of growth and productivity of two collection strains and new Komagataeibacter xylinus C-3 strain on media containing different carbon sources and nutritional supplements under static cultivation conditions were determined. The conditions for surface cultivation of strain, which ensure the maximum level of BC biosynthesis, were selected, and a method for purifiying the film was developed. The optimum nutrient medium for BC gel film formation by the Komagataeibacter xylinus C-3 strain under static culture conditions is the HS medium with 1% glucose, 0.5% ethanol, and 0.1% addition of beer wort. The maximum yield of BC - 7.11 g/l was achieved when the producer was cultivated for 5 days at 30°C. The new strain is more efficient than the collection strains of Gluconoacetobacter xylinus B-11240 and Gluconoacetobacter hansenii B-6756, recommended for industrial production of cellulose. The strainʼs Gen Bank accession number is KU598766.Electron microscopic examination of obtained gel film structural features showed that it consists of microfibrillar bands of nanoscale sizes (15-55 nm). The porous structure of gel film and a high degree of crystallinity provide an excellent mechanical strength to it (17.01 + 0.5 MPa). The film is characterized by high sorption capacity, which allows to hold 11 g of water per 1 g of dehydrated polymer.Bacterial cellulose synthesized by Komagateibacter xylinus C-3 strain under surface culture conditions can be the basis for production of ultra-strong nanocomposite materials in biomedical and other related fields.
Keywords: bacterial cellulose, gel film, Komagataeibacter xylinus